Aging Biomarkers for Evaluating the Life Style Quality of Elderly and Senile People - Gulnur DOSZHANOVA; Aigul ABDULDAYEVA; Kulsara DOSMAMBETOVA (Tehran University of Medical Sciences, 2018)
No Abstract####